The Influence of Slideshow-Based Video Media on Students’ Critical Thinking Skills in the Prehistoric Indonesia Material at SMA Negeri 1 Cikeusal - Arisala, Rian Maulana; Nashar, Nashar; Hadi Wibowo, Tubagus Umar Syarif (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to determine the effect of slideshow-based video media on students’ critical thinking skills in the topic of Prehistoric Indonesia at SMA Negeri 1 Cikeusal in the 2020/2021 academic year. The research employed a quasi-experimental method with purposive sampling. The sample was collected in August–September 2020. Data on students’ critical thinking skills were obtained through pretests and posttests administered to both control and experimental classes. Data were analyzed using a t-test. The findings indicate a significant difference in critical thinking skills between students who used slideshow-based video media and those who did not. The one-tailed t-test at α = 0.05 showed that t calculated exceeded t table, thus rejecting H₀ and accepting Hₐ. It can be concluded that the use of slideshow-based video media has a significant influence on students’ critical thinking skills in the topic of Prehistoric Indonesia.